Models of acute care for injured older patients—Australia and New Zealand practice. Issue 1 (January 2023) - Cubitt, M.; Braitberg, G.; Curtis, K.; Maier, A.B.
Highlights: The model and components of acute care that optimise patient-centred outcomes in injured older patients are not defined. There is variability in models and components of acute care for injured older patients across Australia and New Zealand. Opportunity exists to standardise and validate models of care optimising patient-centred outcomes in injured older patients. Abstract: Introduction: The epidemiology of injured patients has changed, with an increasing predominance of severe injury and deaths in older (65 years and above) patients after low falls. There is little evidence of the models of care that optimise outcomes for injured older patients. This study aims to describe clinician perspectives of existing models of acute care for injured older patients in Australia and New Zealand. Methods: This cross-sectional online survey of healthcare professionals (HCP) managing injured older patients in Australia or New Zealand hospitals was conducted between November 2nd and December 12th, 2020. Recruitment was via survey link and snowball sampling to professional organisations and special interest groups via email and social media. HCP were asked, using a Likert scale, how likely four typical case vignettes were to be admitted to one of twelve options for ongoing care. Additional questions explored usual care components. Results: Participants (n=157) were predominantly Australian medical professionals in a major trauma service (MTS) or metropolitan hospital. The most common age defining "geriatric" was aged 65 years and older (43%). HCP described variability in the models and components of acute care for older injured patients in Australia and New Zealand. As a component of care, cognitive, delirium and frailty screening are occurring (60%, 61%, 46%) with HCP from non-major trauma services (non-MTS) reporting frailty and cognitive impairment screening more likely to occur in the emergency department (ED). Access to an acute pain service was more likely in a MTS. Participants described poor likelihood of a geriatrician (highest 16%) or physician (highest 12%) review in ED Conclusion: Despite a low response rate, HCP in Australia and New Zealand describe variability in acute care pathways for injured older patients. Given the change in epidemiology of injury towards older patients with low force mechanisms, models of acute injury care should be evaluated to define a cost-effective model and components of care that optimise patient-centred outcomes relevant to injured older patients. HCP described some factors they perceive to determine care, and outcomes of variability, offering guidance for future research and resource allocation in the Australia and New Zealand trauma system.